Evaluation of intersystem agreement between standard pelvic organ prolapse quantification system and simplified pelvic organ prolapse scoring system - Singh, Archana G.; Choudhary, Varsha Rani; Ghanghoria, Vineeta; Patel, Kirti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pelvic organ prolapse (POP) is one of the most common gynaecological problem encountered worldwide. The POPQ has become the most commonly used prolapse staging system since its introduction (1996). In spite of having merits to it, POP-Q has not acquired a widespread acceptance. International Urogynaecological Association (IUGA) Standardization of Terminology Committee has devised a simplified version S-POP classification system based on the ordinal stages of the POPQ. The objectives of present study are to determine the intersystem agreement between the standard POPQ and S-POP classification system of pelvic organ prolapse and to propose a user-friendly classification system. Methods: This prospective observational blinded study was conducted in the department of Obstetrics and Gynaecology, NSCB Medical College and Hospital, Jabalpur (M.P.) from March 2015-August 2016. 125 women underwent two separate pelvic examinations POPQ and S-POP, by two groups of gynaecologists at each site. Results were compared and analysed using appropriate statistics. Results: Out of 125 women 54 (43.2%) were in age group 41-50 years. 79 (63.2%) were post-menopausal. 102 (81.4%) were more than third parity. 107 (85.6%) had home delivery. 119 (95.2%) had symptom of something coming out of vagina. The weighted Kappa statistics for the intersystem agreement of S-POP system with POPQ system for overall stage was 0.82, 0.61 for both anterior and posterior vaginal wall, 0.9 for cervix and 0.87 for posterior fornix/cuff. Conclusions: There is significant agreement between the POPQ and S-POP classification systems of POP.